INVESTIGATION OF INFLUENCE OF REGIMES OF THERMAL PROCESSING ON STRUCTURE AND MECHANICAL CHARACTERISTICS OF HOT-ROLLED TUBES, PRODUCED OF STEEL 32G2 - V. V. Ivashko; O. M. Kirilenko; I. I. Vegera; D. A. Semjonov (Литьë и металлургия)
Investigations on influence of heating temperature, cooling regimes and steady temperature on structure and mechanical characteristics of hot-rolled pipes, produced of steel 32G2, are carried out.